Synthesis, modification and application of metal organic frameworks and their derivatives - Mu, Xueliang (2019)
To date, metal-organic frameworks (MOFs) have been developed significantly into numerous applications. This success is primarily attributed to the diversified complete networks created by different synthesis methods. On this basis, a considerable number of modification and transformation strategies are explored to overcome the known limitations of MOFs and to stabilize the active sites, as well as, to add multi-functional species for improving the intrinsic properties of MOFs. In this thesis, several studies, including MOFs preparation, MOFs modification and its possible application are performed to interpret the nature of this material and to identify the suitable material structures for modern industrial process. The first part of this thesis focuses on the preparation of HKUST-1, one of the copper-based MOFs. This preparation adopted a conventional solvothermal method in a reflux unit. In addition, different reaction periods and temperatures have been implicated in the operation of the reflux unit. After pristine HKUST-1 preparation, it is accompanied by an activation process and different temperature of the air dryer for degas purpose. Considering the activation process, it is possible to adjust the textural properties, morphology and size of HKUST-1 crystals through changing the states of HKUST-1 before activation and the types of activation solvents. The focus of this study was to design an optimized method for the synthesis of nano-scale HKUST-1 with high output, large surface area and good CO2 uptake. It was found that the nano-scale HKUST-1 (T85-3-Pm4-120) was successfully synthesized at a yield of 87 % under low temperature of 85 oC using a molar ratio of 6:3:2 for triethylamine(TEA), Cu2+ and trimesic acid (TMA). The highest porosity was achieved after pristine HKUST-1 was activated (powder activation) at 120 oC for four times using methanol. The result showed the optimal HKUST-1 (T85-3-Pm4-120) had a CO2 uptake of 2.5 mmol/g. It is therefore demonstrated that this new approach is a reliable and effective way to synthesize highly porous HKUST-1 MOFs under a mild condition, which is comparable with conventional HKUST-1 by others. The second part of this thesis illustrates the modification of pristine HKUST-1, regarded as post-synthetic modification. In the modification, two distinct strategies were proposed and were adopted. One of them is to incorporate MoS2 quantum dots as a core with a shell of HKUST-1. In this study, a ‘one-pot’ synthesis method was utilized for the growth of HKUST-1 on MoS2 quantum dots to form MoS2/HKUST-1 core-shell hybrid. Before verifying the structure of this hybrid by characterization, a detailed DFT calculation was conducted to assess the possibility of success. Moreover, it proved that the formation of the core-shell composite starts from the adsorption of a Cu2+ cation on a MoS2 quantum dot. This configuration would be followed with the appearance of an intermediate (MoS2+Cu)-TMA structure, which was a configuration of the lowest energy among all possible configurations at this stage. It was also found that MoS2+Cu not only accelerates the deprotonation of trimesic acid, but also stabilizes the structure of HKUST-1 on MoS2. After that, the as-synthesis hybrid was tested on the CO2 adsorption capacity and indicated a good CO2 uptake (4.75 mmol/g) owing to a high surface area (1638.9 m2/g for MH-2). To account for these interactions among them, the secondary building unit (SBU) was modeled to study the mechanism of the adsorption of CO2 on the MoS2/HKUST-1 hybrid. The second strategy of modification is the phase transformation of MOFs utilizing HKUST-1 as a self-sacrificial templet via carbonization/pyrolysis. The annealing process was employed to understand the carbonization process of MOFs. At a fixed heating rate up to 430 °C and an inert atmosphere, the pre-treated HKUST-1 exhibited an expectedly structural stability before 280 oC with noticeable change of pore property. When the temperature continued to rise to 330 oC, the graphitization of the structure led to the formation of Cu nanoparticles. Characterized by the In-situ technology, the acceleration of framework collapse was caused by the presence of local vacancy (unsaturated Cu sites or incomplete protoned carboxylic groups), which is attributed to the break of bridging organic linker. Besides, size and morphology of the resulting materials were influenced by different temperature and prolonged isotherm step under a harsh condition. Thus, this research not only demonstrated the thermal behaviour of HKUST-1 in different temperatures, but also provided an optimized solution for the preparation of CuNP/GO sample. Based on the above-mentioned carbonization mechanism, a series of CuNP/GO catalysts was testified in CO oxidation. The results suggested that CuNP/GO sample (330C-3H), prepared under 330 oC for 3 h, demonstrated a better catalyst performance, and reached a maximum reaction rate at 180 oC (T93 = 180 oC) with an apparent activation energy of 57.17 kJ/mol. To gain a better understanding of the reaction mechanism, the formation of intermediates was monitored using In-situ techniques. The result illustrated that CO molecules preferably bind to the surface of the unstable Cu4O3 phase, in which Cu+ and Cu2+ active sites co-exist. This unique surface property leads to the adsorption of CO and O2 on different positions. Induced by the strong chemical interaction, dissociated oxygen atoms bond to adjacent CO molecule as CO32-. To summarize, in this thesis, HKUST-1 is taken as an example to illustrate in great depth the complete process from the preparation of MOFs, to their modification and applications, covering a wide range of theoretical study and experimental work. In addition, based on the results of the research to date, recommendations for future work were also made at the end of this thesis.